Electrochemical signature of hen egg white lysozyme at the glycerol-modified liquid-liquid interface - Austen, Benjamin; Arrigan, Damien (Pergamon, 2016)
Electrochemical characterization of hen egg white lysozyme (HEWL) at a glycerol-modified interface between two immiscible electrolyte solutions (ITIES) was conducted using a microporous silicon membrane-supported gelled-1,6-dichlorohexane|water-glycerol interface. The electrochemical response of HEWL under these conditions is of interest for the system's potential application to the formation of isorefractive emulsified-ITIES, which offer practical opportunities for spectrophotometric analysis of interfacial processes. Importantly, the voltammetric signature for HEWL seen under glycerol-rich conditions was similar but with some differences from that for glycerol-free conditions. Specifically, the potential at which facilitated transfer of the organic phase electrolyte anion tetrakis-(4-chlorophenyl) borate (TPBCl-) occurred was shifted to lower potential with increasing glycerol concentration. However, features in the voltammetry associated with adsorption/desorption processes were observed to remain constant. The simple ion transfer response of tetraethylammonium cations (TEA+) at the same glycerol-modified ITIES provides insight into the nature of changes that determine the atypical HEWL signature. Lower ion transfer current with respect to increasing glycerol concentration and a shift in transfer potential were the key findings here. The results indicate that the electrochemistry which determines the HEWL signature is similar in environments that are rich in glycerol or purely aqueous.